Produção de etanol pela levedura Saccharomyces bayanus INCQS 40235 a partir do amido de Solanum lycocarpum (lobeira) - Morais, Ricardo Rezende de (2015)
The Solanum lycocarpum plant, commonly known as wolf gray, is a shrub or tree up to 5 m frequent throughout the Brazilian Cerrado, responsible for production wolf fruit. The objective of this work is the use of starch extracted from the fruit of S. lycocarpum as a new source for the production of ethanol by fermentation. The starch in the fruit was extracted by grinding lobeira mesocarp citric acid 0.8% (w / v) subsequent decantation. Thereafter the starch was hydrolyzed using the α-amilise and immobilized glucoamylase-glutaraldehyde polyaniline, with an average rate of glucose production of approximately 80% after 60 h. Glucose solutions at concentrations of 1%, 5% and 9% (w / v) were fermented by the yeast Saccharomyces bayanus INCQS 40235, provided by the National Institute of Quality Control in Health Oswaldo Cruz Foundation. Ethanol production was quantified by the following methods: by reducing the weight due to release of CO2 and the maximum yield obtained after 48 h of fermentation, reaching a production of 6.1704 g in 48 hours; reduction of 75.63% of the total sugar content in the fermentation broth reaching 48.4 mg mL-1 after 48 hours. The fermentation process was also evaluated by the growth of yeast cells that reached 1,407 x 108 cells in 48 hours of fermentation. Results of this work have shown that the starch extracted from the fruit of lobeira is a promising source for the production of ethanol, yielding 10.5% of ethanol after 48h fermentation using a 9% solution of hydrolyzed starch under industrial fermentation simulation.